Effects of high-intensity interval training in combat sports: A systematic review with meta-analysis - Vasconcelos, B. B.; Protzen, G. V.; Galliano, L. M.; Kirk, C.; Del Vecchio, F. B. (The Journal of Strength and Conditioning Research, 2020)
Combat sports (CS) are intermittent by nature and high-intensity interval training (HIIT) has been used as a tool to maintain and improve physical fitness among CS athletes. The aim of this study was to perform a systematic review and meta-analysis about chronic effects of HIIT in CS athletes. An electronic search was performed in PubMed, Science Direct, and Google Scholar using the following Boolean criteria: ("CS" OR "martial arts" OR "judo" OR "taekwondo" OR "jiu jitsu" OR "boxing" OR "karate" OR "wrestling" OR "wushu" OR "kung fu") AND ("HIIT" OR "intermittent exercise" OR "sprint interval training" OR "repeated sprint training [RST]"). To be included, the studies needed to be original, involve CS athletes, present HIIT intervention protocol (HIIT, sprint interval training [SIT] or RST), and analyze chronic physiological outcomes. From 2,211 identified studies, after screening and eligibility evaluation, 12 studies were included in this review with meta-analysis. Aerobic (aerobic capacity, heart rate, and maximum oxygen uptake), anaerobic (peak and mean power in single and successive Wingate tests, and blood lactate concentration), and anthropometric outcomes (body mass and body fat percentage) were evaluated. Data of 255 subjects from 12 studies were assessed. Regarding methodological quality, 7 studies obtained 9-10/12 on the TESTEX scale. For the interventions, 5 studies used HIIT, 4 studies used RST protocols, one used SIT protocols, and one used an intermittent protocol that could not be classified. Relating to aerobic power, was found an increase in V[Combining Dot Above]O2max, with a mean difference (MD) of 2.83 ml/kg·min (CI 95% = 0.40-5.25; p < 0.001) for striking and 2.36 ml/kg·min (CI 95% = 1.05-3.66; p < 0.001) for grappling athletes. No differences on anaerobic peak power for striking (MD = 0.67 W; CI 95% = -0.43 to 1.77; p = 0.23) were found, and a statistical improvement for grappling athletes, (MD = 0.51 W; CI 95% = 0.03-0.98; p = 0.04) was found. Seven studies analyzed anthropometric variables, with differences for body mass in striking (MD = -0.93 kg; CI 95% = -1.68 to -0.19; p = 0.01) and no differences for grappling (MD = -0.09 kg; CI 95% = -2.80 to 2.62; p = 0.95). Differences in body fat percentage in striking (MD = 0.50%; CI 95% = 0.30-0.70; p < 0.001) and no differences in grappling (MD = -0.87%; CI 95% = -1.77 to 0.03; p = 0.06) were found. It was concluded that HIIT positively influences maximum oxygen uptake and anaerobic power in combat sport athletes, with a minor impact on body composition.